Reserve requirements, liquidity risk, and bank lending behavior - Koray Alper; Mahir Binici; Selva Demiralp; Hakan Kara; Pınar Özlü (Koç University-TÜSİAD Economic Research Forum (ERF), 2016)
Although reserve requirements have been used in emerging markets to smooth credit cycles, the exact transmission mechanism remains to be explored. Using bank level data, this study looks inside the black-box to unveil the interaction of reserve requirement policy with bank lending. We identify a new channel that works through a decline in bank liquidity and loan supply due to an increase in reserve requirements. We show that "quantitative tightening" through reserve requirements affect the funding needs and the liquidity position of the banking system. The consequent changes in bank liquidity have a significant impact on the bank lending behavior.
Keywords: E44; E51; E52; 330; monetary transmission mechanism; liquidity channel; reserve requirements; Turkey